Interindividual variability in physical performance adaptations to depth jump training in volleyball players: A study of individualized versus traditional training approaches - Liu, Y.; Guo, J.; Liu, Y. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The purpose of this research was to investigate the impact of an 8-week depth jump (DJ) plyometric training using individualized (I-DJT) or traditional DJ training (T-DJT) methods on the physical performance adaptations of male volleyball players.